Preparation method of lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material for lithium ion battery

Through the preparation of lithium, oxygen, vanadium and carbon co-modified silicon-based anode materials, the problems of low specific capacity of negative electrode materials and volume expansion of silicon-based materials in existing lithium-ion batteries are solved, and electrochemical performance with high specific capacity and good cycle stability is achieved, which is suitable for electric vehicles and energy storage systems.

CN119774618APending Publication Date: 2025-04-08CHINA THREE GORGES UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411783778.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The theoretical specific capacity of graphite negative electrode materials used in existing lithium-ion batteries is low, resulting in limited battery life and energy density of electric vehicles. The volume expansion of silicon-based negative electrode materials during lithiation, resulting in damage to the electrode structure and degradation of electrochemical performance.

Method used

Through the co-modification method of lithium, oxygen, vanadium and carbon elements, Si/LOVC electrode materials were prepared, and by precisely controlling the proportion of raw materials and reaction conditions, a silicon-based negative electrode material with high specific capacity and good cycle stability was formed.

Benefits of technology

It significantly improves the electrochemical cycle stability of lithium-ion batteries, enhances the conductivity and structural stability of the materials, extends the service life of the battery, and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774618A_ABST
    Figure CN119774618A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material, which comprises the following steps: mixing silicon powder with an oxidant, and carrying out oxidation treatment to form a silicon oxide layer; and mixing the oxidized silicon powder with a vanadium source, a lithium source and a carbon source, carrying out ball milling, and carrying out high-temperature sintering on the mixed material to obtain the lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material. By accurately controlling introduction of modified elements and a carbon source, the Si / LOVC negative electrode material prepared by the method shows excellent electrochemical performance, including high specific capacity, good cycling stability and rapid charging and discharging capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The patent of this invention relates to a lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material for lithium-ion batteries and its preparation method. The material is suitable for lithium secondary batteries and belongs to the field of electrochemical power supply technology. Background Art

[0002] In the context of the rapid development of electric vehicles and energy storage industries, lithium-ion batteries, as key energy components in these fields, have a decisive impact on the safety, range and durability of electric vehicles. In order to alleviate the range anxiety of electric vehicles and improve the energy density of energy storage systems, the use of high-specific capacity electrode materials is an effective path. At present, the low theoretical specific capacity (372 mAh / g) of graphite anode materials commonly used in electric vehicle and energy storage system batteries limits the range of electric vehicles and the energy density of energy storage systems, which in turn affects their economic practicality. Silicon-based anode materials are regarded as candidates for the next generation of battery anode materials due to their high theoretical specific capacity (3579 mAh / g) and relatively moderate lithium insertion potential (0.2~0.4V). However, silicon materials undergo significant volume expansion during lithiation, which may lead to the destruction of electrode structure, increase of interfacial impedance and decrease of electrochemical performance, and also pose challenges to battery safety.

[0003] In order to solve these problems, researchers have developed a variety of modification methods for silicon-based negative electrode materials, including nanocrystallization and structural design of silicon-based composite materials. These methods alleviate the volume expansion problem by increasing the specific surface area, providing more active sites, and maintaining the material structure, thereby improving the electrochemical performance. Among the many modification methods, element doping and material surface modification can significantly improve the electrical conductivity and ionic conductivity of silicon-based negative electrode materials, or inhibit the side reactions of silicon with the electrolyte, thereby improving its electrochemical performance. For example, a small amount of phosphorus can be modified into silicon nanoparticles by mechanical ball milling, which can significantly improve the conductivity of silicon. In addition, boron-modified silicon-based composite materials also exhibit excellent electrochemical properties. However, the modification elements currently studied are mainly concentrated on non-metallic elements, which may limit the scope of performance improvement of silicon-based materials.

[0004] The present invention aims to provide a new method for preparing silicon-based negative electrode materials, which improves the electrochemical properties of silicon-based materials by co-modifying lithium, vanadium, oxygen and carbon elements, effectively reducing the side reactions between silicon electrodes and electrolytes and improving the electrochemical properties of materials. The lithium, oxygen, vanadium and carbon modified electrode materials (Si / LOVC) prepared by the present invention exhibit excellent electrochemical cycle stability, providing new possibilities for the large-scale promotion and application of high-performance silicon-based negative electrode materials. Summary of the invention

[0005] The present invention relates to a method for preparing a lithium, oxygen, vanadium, carbon modified electrode material (Si / LOVC), which realizes the preparation of high-performance silicon-based negative electrode materials by precisely controlling the ratio of raw materials and reaction conditions. The preparation process is simple, the manufacturing process is environmentally friendly, the manufacturing cost is low, and there is a good prospect for large-scale commercial application. The following is a specific embodiment of the present invention: Raw material preparation: Choose micron silicon, nano silicon powder, silicon dioxide powder or their mixture as silicon. Choose hydrogen peroxide (H 2 O 2 ), potassium permanganate (KMnO 4 ), potassium perchlorate (KClO 4 ) or a combination of oxidants such as vanadium pentoxide (V 2 O 5 )、Ammonium metavanadate (NH 4 VO 3 ), vanadium dioxide (V 2 O 2 ) and other vanadium sources as vanadium sources. 2 CO 3 )、lithium acetate (CH 3 COOLi) as the lithium source. One or more carbon sources such as asphalt, graphene, carbon nanotubes, expandable graphite, natural graphite, artificial graphite, hard carbon, etc. are selected as the carbon source.

[0006] Raw material ratio: silicon material: oxidant: lithium source: vanadium source: carbon source = (50-100): (1-30): (0.1-10): (0.1-10): (1-30).

[0007] Preparation process: Silicon powder is mixed with a selected oxidant and oxidized to form a silicon oxide layer. The oxidized silicon powder is then mixed with a vanadium source, a lithium source and a carbon source and mixed in a ball mill to ensure uniform dispersion and full contact. The mixed material is sintered at high temperature.

[0008] In addition, the above treatment process may not add a carbon source, or after completing the above sintering step, a carbon source such as asphalt, graphene, etc. may be added to the sintered material, and mechanical fusion may be performed by ball milling to enhance the conductivity and structural stability of the material. In addition, carbonization treatment may be performed after the above mechanical fusion to further improve the electrochemical properties of the material.

[0009] Technical parameters: Ball milling parameters: ball milling time is controlled within 1-48 hours, preferably 10-24 hours. Carbonization process parameters: reaction temperature 350-1500°C, preferably 550-950°C; reaction time 3-48 hours, preferably 5-12 hours. The carbonization process uses one or more mixtures of commonly used protective gases such as nitrogen, hydrogen, argon, etc.

[0010] Technical advantages: The present invention oxidizes silicon, modifies it with lithium, oxygen, and vanadium, and introduces a carbon source, which not only dopes silicon with elements to improve the electrochemical kinetic properties of silicon; at the same time, by adjusting the raw materials and their proportions, a protective film can be selectively generated on the silicon surface to reduce the side reactions between silicon active substances and electrolytes, thereby improving the stability of the material. This method adheres to the principles of green environmental protection in the selection and preparation of raw materials, does not produce toxic waste, and meets the requirements of sustainable development. The preparation process of this method is simple, the required equipment is easy to operate, and the manufacturing cost is relatively low, which is suitable for industrial large-scale production. By precisely controlling the introduction of modifying elements and carbon sources, the Si / LOVC negative electrode material prepared by the present invention exhibits excellent electrochemical properties, including high specific capacity, good cycle stability, and fast charge and discharge capabilities.

[0011] Through these innovations, the present invention aims to provide a new economical and environmentally friendly approach for the preparation of battery negative electrode materials to meet the growing demand for energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 : XRD spectrum of Si / LOVC and silicon in Example 1.

[0013] Figure 2 : XRD spectra of Si / LOVC and silicon in Example 2.

[0014] Figure 3 : XRD spectrum of Si / LOVC and silicon of Example 3.

[0015] Figure 4 : XRD spectrum of Si / LOVC and silicon of Example 4.

[0016] Figure 5 : XRD spectrum of Si / LOVC and silicon in Example 5.

[0017] Figure 6 : TEM image of Si / LOVC.

[0018] Figure 7 : Cyclic stability curves of Si / LOVC and Si of Examples 1-5.

[0019] Figure 8: Cyclic stability curves of Si / LOVC and micron Si of Comparative Examples 1-4 and Example 1. DETAILED DESCRIPTION

[0020] This article aims to explore the technical details of the present invention in depth, covering examples and control groups to reveal the characteristics and potential advantages of lithium, oxygen, vanadium, and carbon modified electrode materials (Si / LOVC). It should be emphasized that the examples listed are not exhaustive of all possible implementation methods. Any new examples derived from the examples of the present invention, as long as they do not involve innovative changes, should also be regarded as the scope of protection of the present invention. In order to more intuitively present the preparation process of the present invention, Example 2 mainly adjusts the process sequence of preparing Si / LOVC in Example 1, Example 3 mainly adjusts the raw materials for preparing Si / LOVC in Example 1, Example 4 mainly adjusts the raw material ratio of preparing Si / LOVC in Example 1, and Example 5 mainly adjusts the key process parameters for preparing Si / LOVC in Example 1. Example 6 mainly tests and analyzes the electrochemical performance of Si / LOVC and micron silicon powder prepared in Examples 1-5. Control groups 1 to 4 do not contain silicon surface oxidation, lithium source, vanadium source, and carbon source, respectively.

[0021] Example 1: Add 1 gram of micron silicon (material particle size D50 is 1-30 μm) to a beaker containing 100 mL of deionized water, stir with a magnetic stirrer for 30 minutes, then add 1 g of oxidant hydrogen peroxide solution (35 wt.%), stir with a magnetic stirrer for 360 minutes, filter and dry, wash three times with a large amount of ionized water, and then dry to obtain surface-oxidized silicon powder. The surface-oxidized silicon powder is mixed with 0.05 g of vanadium pentoxide, 0.05 g of lithium carbonate and 0.05 g of asphalt, and mixed by a ball mill for 10 hours, a rotation speed of 400 rpm, and a ball-to-material mass ratio of 30:1. The mixed material is then sintered at a high temperature, with a sintering temperature of 600°C, a sintering time of 5 hours, and a sintering atmosphere of nitrogen. The obtained sample is named Si@LSO@C.

[0022] The X-ray diffraction (XRD) spectra of the Si / LOVC sample of this embodiment and the untreated Si of this embodiment are shown in Figure 1 . Si / LOVC and Si material both show characteristic diffraction peaks at 28°, 47°, 56°, 69°, and 76°. In addition, compared with the silicon material, the peak position of Si / LOVC shifts to the left, which indicates that the interplanar spacing of silicon increases after the silicon material is treated in Example 1, which will be beneficial to the diffusion of lithium ions in silicon, thereby improving the kinetic transmission performance of silicon materials. In addition, the transmission electron microscope (TEM) analysis of the sample Si / LOVC of this example shows that a carbon coating layer with a thickness of about 20nm is generated on the silicon surface. The TEM image is shown in FIG. Figure 6 .

[0023] Example 2: Compared with Example 1, no carbon source is added in the first ball milling process, and carbon coating treatment is performed again after sintering. The specific steps are as follows: 1 gram of micron silicon (material particle size D50 is 1-30 μm) is added to a beaker containing 100 mL of deionized water, stirred with a magnetic stirrer for 30 minutes, and then 1 g of oxidant hydrogen peroxide solution (35 wt.%) is added, stirred with a magnetic stirrer for 360 minutes, filtered and dried, washed three times with a large amount of ionized water, and then dried to obtain surface-oxidized silicon powder. The surface-oxidized silicon powder is mixed with 0.05 g of vanadium pentoxide and 0.05 g of lithium carbonate, and mixed by a ball mill, the ball milling time is 10 hours, the rotation speed is 400 rpm, and the ball-to-material mass ratio is 30:1. The mixed material is then sintered at a high temperature, the sintering temperature is 600°C, the sintering time is 5 hours, and the sintering atmosphere is nitrogen, and the sintered product S1 is obtained. Subsequently, 0.5 g of S1 was mixed with 25 mg of asphalt and mixed by ball milling for 10 hours at a speed of 400 rpm and a ball-to-material mass ratio of 30:1. The mixed material was then sintered at a high temperature of 600 °C for 5 hours in a nitrogen atmosphere, and the obtained sample was named Si@LSO@C.

[0024] The X-ray diffraction (XRD) spectra of the Si / LOVC sample of this embodiment and the untreated Si of this embodiment are shown in Figure 2 . Si / LOVC and Si materials both show characteristic diffraction peaks at 28°, 47°, 56°, 69°, and 76°. In addition, compared with the silicon material, the peak position of Si / LOVC shifts to the left, which indicates that the interplanar spacing of silicon increases after the silicon material is treated in Example 2, which will be beneficial to the diffusion of lithium ions in silicon, thereby improving the kinetic transmission performance of silicon materials.

[0025] Example 3: Compared with Example 1, the types of oxidant, lithium source, vanadium source and carbon source in the raw materials are adjusted. 1 gram of micron silicon (material particle size D50 is 1-30 μm) is added to a beaker containing 100 mL of deionized water, stirred with a magnetic stirrer for 30 minutes, and then 0.3 g of potassium permanganate is added, stirred with a magnetic stirrer for 360 minutes, filtered and dried, washed three times with a large amount of ionized water, and then dried to obtain surface-oxidized silicon powder. The surface-oxidized silicon powder is mixed with 0.05 g of ammonium metavanadate, 0.05 g of lithium hydroxide and 0.05 g of natural graphite, and mixed by a ball mill, the ball milling time is 10 hours, the rotation speed is 400 rpm, and the ball-to-material mass ratio is 30:1. The mixed material is then sintered at high temperature, the sintering temperature is 600°C, the sintering time is 5 hours, and the sintering atmosphere is nitrogen. The obtained sample is named Si@LSO@C.

[0026] The X-ray diffraction (XRD) spectra of the Si / LOVC sample of this embodiment and the untreated Si of this embodiment are shown in Figure 3 . Si / LOVC and Si materials both show characteristic diffraction peaks at 28°, 47°, 56°, 69°, and 76°. In addition, compared with the silicon material, the peak position of Si / LOVC shifts to the left, which indicates that the interplanar spacing of silicon increases after the silicon material is treated in Example 3, which will be beneficial to the diffusion of lithium ions in silicon, thereby improving the kinetic transmission performance of silicon materials. In addition, new phases other than silicon appear in the samples of this example.

[0027] Example 4: 1 gram of micron silicon (material particle size D50 is 1-30 μm) was added to a beaker containing 100 mL of deionized water, stirred with a magnetic stirrer for 30 minutes, and then 0.03 g of oxidant hydrogen peroxide solution (35 wt.%) was added, stirred with a magnetic stirrer for 360 minutes, filtered and dried, washed three times with a large amount of ionized water, and then dried to obtain surface-oxidized silicon powder. The surface-oxidized silicon powder was mixed with 0.08 g of vanadium pentoxide, 0.08 g of lithium carbonate and 0.08 g of asphalt, and mixed by a ball mill for 10 hours, a rotation speed of 400 rpm, and a ball-to-material mass ratio of 30:1. The mixed material was then sintered at a high temperature, with a sintering temperature of 600°C, a sintering time of 5 hours, and a sintering atmosphere of nitrogen. The obtained sample was named Si@LSO@C.

[0028] The X-ray diffraction (XRD) spectra of the Si / LOVC sample of this embodiment and the untreated Si of this embodiment are shown in Figure 4 . Si / LOVC and Si materials both show characteristic diffraction peaks at 28°, 47°, 56°, 69°, and 76°. In addition, compared with silicon materials, the diffraction peaks of Si / LOVC do not shift significantly, which indicates that the interplanar spacing of silicon does not change significantly after the silicon material is treated in Example 4, which indicates that the ratio of the raw materials determines the effect of silicon doping.

[0029] Example 5: 1 gram of micron silicon (material particle size D50 is 1-30 μm) is added to a beaker containing 100 mL of deionized water, stirred with a magnetic stirrer for 60 minutes, and then 1 g of oxidant hydrogen peroxide solution (35 wt.%) is added, stirred with a magnetic stirrer for 60 minutes, filtered and dried, washed three times with a large amount of ionized water, and then dried to obtain surface-oxidized silicon powder. The surface-oxidized silicon powder is mixed with 0.05 g of vanadium pentoxide, 0.05 g of lithium carbonate and 0.05 g of asphalt, and mixed by a ball mill for 2 hours, a rotation speed of 200 rpm, and a ball-to-material mass ratio of 10:1. The mixed material is then sintered at a high temperature, with a sintering temperature of 700°C, a sintering time of 12 hours, and a sintering atmosphere of nitrogen. The obtained sample is named Si@LSO@C.

[0030] The X-ray diffraction (XRD) spectra of the Si / LOVC sample of this embodiment and the untreated Si of this embodiment are shown in Figure 5 . Si / LOVC and Si materials both show characteristic diffraction peaks at 28°, 47°, 56°, 69°, and 76°. In addition, compared with the silicon material, the diffraction peak of Si / LOVC shifts to the left, which indicates that the interplanar spacing of silicon increases after the silicon material is treated in Example 4, which will be beneficial to the diffusion of lithium ions in silicon, thereby improving the kinetic transmission performance of silicon materials.

[0031] Example 6: The button cell tests were performed on the samples Si / LOVC of Examples 1-5 and the untreated micron Si to evaluate their capacity and charge-discharge cycle characteristics. The button cell preparation steps for all samples in the present invention are as follows: the active material, the conductive agent Super-P and the binder SBR are mixed in a mass ratio of 80:10:10 and dissolved in water to form a slurry. Subsequently, the slurry is evenly coated on the surface of the copper foil and dried in a vacuum environment for 14 hours. Metal lithium foil is used as the negative electrode, and a polypropylene separator (PP, 16 microns) and an electrolyte (the solvent ratio is DMC:EMC:EC=3:3:2, the LiPF6 concentration is 1.05M, and FEC accounts for 10% of the total volume of the electrolyte) are assembled into a 2025-type button cell. When performing charge and discharge tests, the current density is set to 1.0 A / g, and the voltage window is set between 0.01 and 1.5V. See the test results. Figure 7 , the cycle stability of Si / LOVC in Examples 1-5 is significantly improved compared with the untreated micron Si.

[0032] Comparative Example 1: The reaction raw materials are similar to those in Example 1, but no oxidant is added. Specifically, 1 gram of micron silicon (material particle size D50 is 1-30 μm) is mixed with 0.05 g of vanadium pentoxide, 0.05 g of lithium carbonate and 0.05 g of asphalt, and mixed by a ball mill for 10 hours, a rotation speed of 400 rpm, and a ball-to-material mass ratio of 30:1. The mixed material is then sintered at a high temperature of 600°C, a sintering temperature of 5 hours, and a sintering atmosphere of nitrogen.

[0033] Comparative Example 2: The reaction raw materials are similar to those in Example 1, but no lithium source is added. Specifically, 1 gram of micron silicon (material particle size D50 is 1-30 μm) is added to a beaker containing 100 mL of deionized water, stirred with a magnetic stirrer for 30 minutes, and then 1 g of the oxidant hydrogen peroxide solution (35 wt.%) is added, stirred with a magnetic stirrer for 360 minutes, filtered and dried, washed three times with a large amount of ionized water, and then dried to obtain surface-oxidized silicon powder. The surface-oxidized silicon powder is mixed with 0.05 g of vanadium pentoxide and 0.05 g of asphalt, and mixed by a ball mill, with a ball milling time of 10 hours, a rotation speed of 400 rpm, and a ball-to-material mass ratio of 30:1. The mixed material is then sintered at a high temperature, with a sintering temperature of 600°C, a sintering time of 5 hours, and a sintering atmosphere of nitrogen.

[0034] Comparative Example 3: The reaction raw materials are similar to those in Example 1, but no vanadium source is added. Specifically, 1 gram of micron silicon (material particle size D50 is 1-30 μm) is added to a beaker containing 100 mL of deionized water, stirred with a magnetic stirrer for 30 minutes, and then 1 g of the oxidant hydrogen peroxide solution (35 wt.%) is added, stirred with a magnetic stirrer for 360 minutes, filtered and dried, washed three times with a large amount of ionized water, and then dried to obtain surface-oxidized silicon powder. The surface-oxidized silicon powder is mixed with 0.05 g of lithium carbonate and 0.05 g of asphalt, and mixed by a ball mill, with a ball milling time of 10 hours, a rotation speed of 400 rpm, and a ball-to-material mass ratio of 30:1. The mixed material is then sintered at a high temperature, with a sintering temperature of 600°C, a sintering time of 5 hours, and a sintering atmosphere of nitrogen.

[0035] Comparative Example 4: The reaction raw materials are similar to those in Example 1, but no carbon source is added. Specifically, 1 gram of micron silicon (material particle size D50 is 1-30 μm) is added to a beaker containing 100 mL of deionized water, stirred with a magnetic stirrer for 30 minutes, and then 1 g of the oxidant hydrogen peroxide solution (35 wt.%) is added, stirred with a magnetic stirrer for 360 minutes, filtered and dried, washed three times with a large amount of ionized water, and then dried to obtain surface-oxidized silicon powder. The surface-oxidized silicon powder is mixed with 0.05 g of vanadium pentoxide and 0.05 g of lithium carbonate, and mixed by a ball mill for 10 hours, a rotation speed of 400 rpm, and a ball-to-material mass ratio of 30:1. The mixed material is then sintered at a high temperature, with a sintering temperature of 600°C, a sintering time of 5 hours, and a sintering atmosphere of nitrogen.

[0036] Comparative Example 5: The Si / LOVC samples of Comparative Examples 1-4 and Example 1 were tested with untreated micronized Si in button cells to evaluate their capacity and charge-discharge cycle characteristics. The sample preparation and test methods were the same as those of Example 6. The test results are shown in Figure 8 .

[0037] Specific capacity: Example 1 > Comparative Example 4 > Comparative Example 2 > Comparative Example 1 > Micron silicon > Comparative Example 3 Cyclic stability: Example 1 > Comparative Example 3 > Comparative Example 4 > Comparative Example 2 > Comparative Example 1 > micron silicon.

Claims

1. A method for preparing a lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material, characterized in that: The steps include: The silicon powder is mixed with an oxidant and oxidized to form an oxide layer of silicon; The oxidized silicon powder is then mixed with a vanadium source, a lithium source and a carbon source, and the mixed material is sintered at high temperature through ball milling to obtain a lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material.

2. The method for preparing a lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material according to claim 1, characterized in that: The oxidized silicon powder is mixed with a vanadium source and a lithium source, and the mixed material is sintered at high temperature through ball milling. The sintered product is then added with a carbon source for ball milling, and selectively sintered again or not sintered to obtain a lithium, vanadium, oxygen, and carbon co-modified silicon composite negative electrode material.

3. The method for preparing a lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material according to claim 1, characterized in that: The silicon powder is selected from micron silicon, nano silicon powder, silicon oxide powder or a mixture thereof.

4. The method for preparing a lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material according to claim 1, characterized in that: The oxidant includes one or a combination of hydrogen peroxide, potassium permanganate and potassium perchlorate as the oxidant.

5. The method for preparing a lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material according to claim 1, characterized in that: The vanadium source includes one or more of vanadium pentoxide, ammonium metavanadate, and vanadium dioxide as the vanadium source; The lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium acetate as the lithium source; The carbon source includes one or more of asphalt, graphene, carbon nanotubes, expandable graphite, natural graphite, artificial graphite and hard carbon.

6. The method for preparing a lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material according to claim 1, characterized in that: The ball milling process is performed at 500-1000 r / min for 1-48 hours, preferably 10-24 hours.

7. The method for preparing a lithium, vanadium, oxygen and carbon co-modified silicon composite negative electrode material according to claim 1, characterized in that: The high temperature sintering process parameters are: reaction temperature 350-1500°C, preferably 550-950°C; reaction time 3-48 hours, preferably 5-12 hours; The high temperature sintering process is carried out in any protective gas of nitrogen, hydrogen and argon.

8. Lithium, vanadium, oxygen, and carbon co-modified silicon composite negative electrode material, characterized in that: The negative electrode material prepared by the method according to any one of claims 1 to 7 has characteristic diffraction peaks at about 28.3±0.2°, 47±0.2°, 56±0.2°, 69±0.2°, and 76±0.2°, and a carbon coating layer with a thickness of 10-20 nm is generated on the silicon surface.

9. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material is prepared by the method according to any one of claims 1 to 7.

10. A lithium secondary battery, characterized in that: The negative electrode material is prepared by the method according to any one of claims 1 to 7.